Emerging Strategies in Classroom Management: Impact on the 21st Century Skills Competency of Grade 10 Students - Dailo, Rossana R.; Dailo, Alfred E. (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
The study was an attempt to determine if there is a significant relationship between teachers’ use of different classroom management strategies and the 21st-century skills competency of Grade 10 students. This research used a random sampling technique to determine the specific number of student respondents to the study. A self-made survey questionnaire was developed in this study. The researcher sought the assistance of different research professionals, master teachers in English, and experts in the field to validate the research instrument. The following are the findings of the study: The extent of utilization of teachers on preventive, supportive, and corrective classroom management strategies are all interpreted as utilized. The levels of students’ learning and innovation skills, life and career skills, and information, media, and technology skills are interpreted as very good. There is a significant relationship between classroom management strategies and the skills competency of the students. And classroom management strategies are significant predictors of students’ 21st skills competency.